PENGARUH KARAKTERISTIK PERUSAHAAN DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK: PENGHINDARAN PAJAK - Risma Indah Permata Sari (JEKOS (Jurnal Ekonomi Dan Sosial), 2026)
This study aims to analyze the effect of company characteristics proxied by leverage, firm size, and profitability, as well as transfer pricing on tax avoidance. Tax avoidance is a company’s effort to legally minimize tax burdens by exploiting loopholes in applicable tax regulations. This research employs a quantitative method using secondary data derived from the financial statements of companies included in the IDX30 index listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Data analysis was conducted using panel data regression with statistical software. Tax avoidance was measured using the Effective Tax Rate (ETR). The results indicate that leverage, firm size, profitability, and transfer pricing simultaneously affect tax avoidance. Partially, leverage, firm size, profitability, and transfer pricing have an influence on tax avoidance. This study is expected to contribute to the development of accounting and taxation knowledge and to serve as a reference for companies and policymakers in formulating corporate tax management strategies. Keywords: Tax Avoidance, Leverage, Firm Size, Profitability, Transfer Pricing.